Food habits of bats of subfamily vampyrinae in Brazil - Bonato, V; Facure, K. G.; Uieda, W. (Alliance Communications Group Division Allen Press, 2004)
We describe and compare diets of 3 species of vampyrine bats based on analysis of food remains found in gastrointestinal tracts of preserved museum specimens. We also examined possible ontogenetic, intersexual, geographic, and seasonal variations in feeding habits of each species. Trachops cirrhosus fed mainly on insects (79% of prey items), whereas Chrotopterus auritus and Vampyrum spectrum primarily ate small vertebrates (61-73% of prey items for both species). Vertebrate prey most frequently eaten by C. auritus were murid rodents whereas V. spectrum consumed primarily passerine birds. The frequency of occurrence of food items did not differ significantly with age or sex, at least for T. cirrhosus and C. auritus. Significant seasonal variations in diet were observed only for C. auritus, which consumed more insects during the wet season. Our findings confirm the importance of insects in the diet of T. cirrhosus and present new information on a diversified diet for V. spectrum and opportunistic feeding for C. auritus.
Keywords: Chrotopterus auritus; food habits; Trachops cirrhosus; Vampyrum spectrum